Reflector localization for geometrical modeling the air-ground channel - Schneckenburger, Nicolas; Jost, Thomas; Shutin, Dmitriy; Walter, Michael; Del Galdo, Giovanni; Fiebig, Uwe Carsten (IEEE Transactions on Vehicular Technology, 2018)
In the air-ground propagation channel, multipath propagation severely affects the performance of the communication, navigation, and surveillance systems used in civil aviation. To gain a deeper understanding of the air-ground channel, we are interested in the locations of objects causing multipath propagation. Therefore, in this paper we propose and experimentally validate an algorithm to localize reflectors causing multipath components based on channel sounding data collected using omnidirectional antennas. The algorithm relies on superresolution parameter estimation and tracking as well as on a localization algorithm. Using both simulations and channel sounding data collected from flight trials, we demonstrate the ability to reliably localize the reflectors causing multipath components.
CRIS-Team Scopus Importer:2025-11-10
Keywords: Channel models; Multipath channels; Parameter estimation; Propagation